2015
DOI: 10.4103/0019-5278.174002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived heat stress and health effects on construction workers

Abstract: Introduction:Increasing heat waves-particularly in urban areas where construction is most prevalent, highlight a need for heat exposure assessment of construction workers. This study aims to characterize the effects of heat on construction workers from a site in Gandhinagar.Materials and Methods:This study involved a mixed methods approach consisting of a cross sectional survey with anthropometric measurements (n = 219) and four focus groups with construction workers, as well as environmental measurements of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…For meta-analyses five and six, GRADE analysis revealed that the true effect is likely to be substantially different from the estimate of effect (very low confidence). Most (68%) 4,6,26,[33][34][35][39][40][41][42][43]45,46,[50][51][52][53][54][55]56,57, of the included studies incorporated low risk for selection bias, with the remaining studies presenting selection bias that was non-applicable (10%), 36, unclear (16%), 37,[47][48][49]118,[127][128][129][130][131][132] or, in some cases, high risk (6%) 5,38,44,133 due to acrossgroup variation in inclusion or exclusion criteria, and across-group differences in participant recruitment or selection. Most (61%) of the included studies incorporated low risk for confounding factors bias, with the remaining studies presenting confounding factor bias that was unclear (16%) 6 ,26,36,38,60,62,63,67,80,84,85,92,98-100,102,105,107-111,113,114,134-136 or high risk (23%) 33 ,35,37,44,45,47,49,59,66,74,83,86,89,91,94,96,118,127,128,132…”
Section: Resultsmentioning
confidence: 99%
“…For meta-analyses five and six, GRADE analysis revealed that the true effect is likely to be substantially different from the estimate of effect (very low confidence). Most (68%) 4,6,26,[33][34][35][39][40][41][42][43]45,46,[50][51][52][53][54][55]56,57, of the included studies incorporated low risk for selection bias, with the remaining studies presenting selection bias that was non-applicable (10%), 36, unclear (16%), 37,[47][48][49]118,[127][128][129][130][131][132] or, in some cases, high risk (6%) 5,38,44,133 due to acrossgroup variation in inclusion or exclusion criteria, and across-group differences in participant recruitment or selection. Most (61%) of the included studies incorporated low risk for confounding factors bias, with the remaining studies presenting confounding factor bias that was unclear (16%) 6 ,26,36,38,60,62,63,67,80,84,85,92,98-100,102,105,107-111,113,114,134-136 or high risk (23%) 33 ,35,37,44,45,47,49,59,66,74,83,86,89,91,94,96,118,127,128,132…”
Section: Resultsmentioning
confidence: 99%
“…Individual and environmental factors such as adaptive behavior, gender, socioeconomic status, access to health care, and building structure have been shown to contribute to the adverse health effects of heat ( Dutta et al 2015 ; Eisenman et al 2016 ; Hondula et al 2012 ; Laverdière et al 2016 ; Näyhä et al 2016 ; Smith et al 2014 ; Son et al 2016 ; Vandentorren et al 2004 ). We still know little, however, about the role of these factors in exacerbating vulnerability to cold in low- and middle-income countries, where low temperature usually is not given priority as a health risk.…”
Section: Discussionmentioning
confidence: 99%
“…The survey (Annex 1) was an adapted version of the original one developed by Kjellstrom et al within the “Hothaps programme”, a multi-centre health research and prevention programme aimed at quantifying the extent to which working people are affected by, or adapt to, heat exposure in the workplace, and climate change role in increasing such effects [20]. The original version was also used also by Dutta et al to characterize the effects of heat on construction workers from a site in Gandhinagar, India [21]. The estimated time to complete the questionnaire was around ten minutes.…”
Section: Methodsmentioning
confidence: 99%